The HPLC-MS handbook for practitioners - Kromidas, Stavros (Wiley-VCH, 2017)
Filling the gap for an expert text dealing exclusively with the practical aspects of HPLC-MS coupling, this concise, compact, and clear book provides detailed information to enable users to employ the method most efficiently. Following an overview of the current state of HPLC-MS and its instrumentation, the text goes on to discuss all relevant aspects of method development. A chapter on tips and tricks is followed by user reports on the advantages - and pitfalls - of applying the method in real-life scenarios. The whole is rounded off by a look at future developments by renowned manufacturers.
Keywords: High performance liquid chromatography -- Handbooks, manuals, etc.; Mass spectrometry -- Handbooks, manuals, etc.; elektronické knihy; electronic books